Pengaruh Daun Katuk (Sauropus androgynus (L.) Merr.) terhadap Waktu Perdarahan (Bleeding Time) pada Tikus Wistar Jantan sebagai Alternatif Obat Antitrombotik (The Effect of Star Gosseberry (Sauropus androgynus (L.) Merr.) to bleeding time of Male Wistar - Selvia Magdalena; Budi Yuwono; Agustin Wulan Suci Dharmayanti (UPT Percetakan dan Penerbitan Universitas Jember, 2015)
Background: Cardiovascular disease can be treated with synthetic or traditional antithrombotic drugs (herbal). Synthetic antithrombotic drugs have a lot of side effects, so as an alternative antithrombotic is used traditional drugs, star gosseberry. Star gosseberry have many active compounds which are suspected to inhibit platelet aggregation. Objective: to know the effect of star gosseberry on bleeding time of male Wistar rats as an alternative antithrombotic drugs. Methods of research: this study was experimental laboratory research with post-test only control group design. The research samples were 24 male wistar rats and divided into 4 groups: negative control (distilled water), positive control (aspirin 5,85 mg dose), treatment 1 (star gosseberry 4,5 mg/g dose), and treatment 2 (star gosseberry 2.25 mg/g dose). The treatment was given for 8 days then the tail of samples were cut by 0.5 cm from the tip of the tail. Every 30 seconds the blood that dripped out was absorbed on absorbent papers until the bleeding stops. Bleeding time was measured from initial point of bleeding until the cessation of the bleeding point. Result: star gosseberry dose 4,5 mg/g had the same effect as aspirin that was prolonged bleeding time. Conclusion: star gosseberry could be prolonged bleeding time so it can be used as an alternative antithrombotic drugs. Keywords: Katuk leaf, bleeding time, antithrombotic, platelet